Da sentença que reconhece a existência de obrigação como título executivo (CPC, Art.475 N, I) - Iglesias, André de Freitas (2007)
The present study is destined to analyze the meaning of the new content of interpolated proposition I of the article 475-N of the Civil Procedure Code. Due to the generic terms that have been used, the article has caused unreliability, because it seems there is no longer clear criteria to identify a sentence that allows enforcement. The objective is, therefore, to clarify the nature of the sentence mentioned in the related article. Firstly it is made an analysis of the concepts of conviction and declaratory judgements based on their contents. Later it is analyzed the constitutionality of the legislative alteration, the inconveniences that would be caused by the adoption of the declaratory judgement as enforceable judgement and the meaning of a sentence that denies a negative declaratory claim. In conclusion, the sentence that allows enforcement continues to be the conviction judgement